The Role of Human Capital Toward Regional Economic Growth in Java - Anwar, Aminuddin (Jurnal Economia, 2017)
Abstract: The Role of Human Capital Toward Regional Economic Growth in Java. The aim of this study is to provide empirical evidence of the central role of human capital in economic growth. The contribution of this study is focused on Java island as a center of economic activities in Indonesia that needs to be analyzed the contribution of human capital development to the growth of regional economies. This study uses panel data on 114 counties and cities in Java during the period 2004-2013. Human capital indicators employed in this study is the average length of school for education and life expectancy for health. The estimation results indicate that education and health have a positive contribution to regional economic growth. Its shows the critical role of education as one of the primary sources to achieve better economic development. Another finding of this study is the positive role of investment and tends to be a negative contribution of the fiscal decentralization. Keywords: Regional Economic Growth, Human Capital, Panel Data, JavaAbstrak: Peran Modal Manusia Terhadap Pertumbuhan Ekonomi Regional di Jawa. Penelitian ini bertujuan untuk memberikan bukti empiris peran sentral modal manusia terhadap pertumbuhan ekonomi. Kontribusi tersebut difokuskan di Pulau Jawa karena menjadi pusat aktivitas perekonomian di Indonesia sehingga perlu dianalisis kontribusi pengembangan modal manusia terhadap pertumbuhan ekonomi regional. Penelitian ini menggunakan metode panel data pada 114 kabupaten dan kota di Pulau Jawa selama periode 2004-2013. Indikator modal manusia yang digunakan dalam penelitian ini adalah rata-rata lama sekolah untuk pendidikan dan angka harapan hidup untuk kesehatan. Hasil estimasi menunjukkan bahwa pendidikan dan kesehatan memiliki kontribusi positif terhadap pertumbuhan ekonomi regional. Hal ini mengindikasikan peran penting pendidikan sebagai salah satu sumber utama untuk mencapai pembangunan ekonomi yang lebih baik. Temuan lain dari penelitian ini adalah adanya peran positif dari investasi dan kontribusi yang cenderung negatif dari adanya desentralisasi fiskal. Kata kunci: Pertumbuhan Ekonomi Regional, Modal Manusia, Panel Data, Jawa